Students’ Hobbies as a Context for Physics Teaching - Chalupková, Soňa; Demkanin, Peter (Scientia in educatione, 2013)
Every young person has a lot of hobbies. There, like in all everyday activities, he/she applies physical phenomena – either intentionally or unwittingly. The article deals with one of the possibilities of how to include students’ out-of-school knowledge in formal school education in physics at high school. Students were given an assignment: to write a report and prepare a presentation about their free time activity. The hobby played the role of a mediator between physics and relaxed free time. The questionnaire given at the end of all the presentations points out the fact that the students enjoyed preparing their own reports, it was an enriching process for them, but they were not so sure whether their reports had also been beneficial for the others.